Kajian Material ASME SA-533 Dengan Standar ASME Section VIII Divisi 2 Pada Bejana Tekan Amine Gas Treatment - Imron, Jefri; Setyanto, Djoko (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2023)
The oil and gas sector is one of the main sectors for the Indonesian economy. To get good gas, there is a natural gas separation process through Amine Gas Treating/Acid Gas Treating using a pressure vessel. However, the condition of FPSOs located offshore makes them face various environmental burdens. This research aims to examine the substitution of pressure vessel material design using ASME SA-533 Type E Class 2 (P-No. 3) material for sour gas service with the same design parameters. Material design was carried out using PV Elite. The results show that there are chemical and mechanical differences between the ASME SA-516 Gr-70 material and the ASME SA-533 Type E Class 2 material. The same thing can also be seen in the efficiency of the material elements, which consist of shell thickness, bottom head, upper head , and the weight of the pressure vessel shows that the ASME SA-533 Type E Class 2 material is more efficient than the ASME SA-516 Gr-70 material. SA 533-Type E material shows results in pressure vessel weight savings with an estimate of 44.7% and total material price savings of 44.40%. Material substitution certainly not only has an impact on the efficiency of pressure vessel weight, but also has an impact on reducing operational costs used to support production processes in the oil and gas industry.